2007
DOI: 10.3349/ymj.2007.48.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Higher-Order Aberration and Contrast Sensitivity in Monofocal and Multifocal Intraocular Lenses

Abstract: PurposeThe visual performance of pseudophakic eyes depends on the type of intraocular lenses (IOLs) that are implanted. Aspherical and multifocal IOLs have recently been developed to improve visual quality after cataract surgery, but multifocal IOLs can be associated with decreased contrast sensitivity (CS), halos, and glare. This study compares the visual performance of monofocal and multifocal IOLs by measurement of higher-order aberrations (HOAs) and CS values.Materials and MethodsHOAs and CS values of 42 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…This is because of the division of light energy through two focal points produced by a multifocal IOL 9. In our study, contrast sensitivity values were lower in diffractive multifocal group as compared to accommodative group; however, there was no significant reduction in contrast ( P = 0.3919).…”
Section: Discussioncontrasting
confidence: 53%
“…This is because of the division of light energy through two focal points produced by a multifocal IOL 9. In our study, contrast sensitivity values were lower in diffractive multifocal group as compared to accommodative group; however, there was no significant reduction in contrast ( P = 0.3919).…”
Section: Discussioncontrasting
confidence: 53%
“…Overall, when compared to monofocal lenses, MIOL implantation has been reported to result in compromised CS values, particularly at high spatial frequencies and mesopic conditions (4–6, 8), although some authors have documented an improvement over time, with CS values approaching normality 3 to 6 months after surgery (7, 18). Comparisons between multifocal designs have revealed a superior performance of diffractive over refractive lens designs, with aspheric profiles proving beneficial in mesopic conditions as a means of counteracting the increase in high-order aberrations (mostly spherical aberration) resulting from pupil dilation (1317).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the case-control and cohort with control studies were similar to those of the RCTs; most found some advantage in contrast sensitivity with monofocal lenses compared to multifocal lenses. Early studies of refractive and diffractive IOLs including the Array lens reported a reduction in contrast sensitivity compared to monofocal controls under most conditions (464748495051), at the lower levels of Regan contrast conditions (26, 35, 525354), low frequency (55), or under adverse testing conditions such as glare (56), low luminance (57), or low luminance with glare (58). One study of the Array lens suggested that patients have an initial reduction in contrast sensitivity that improves over time postoperatively, whereas the monofocal group achieved stable normal contrast sensitivity values early in the postoperative course (59).…”
Section: Resultsmentioning
confidence: 99%